Serum IL-33 Level and IL-33, IL1RL1 Gene Polymorphisms in Asthma and Multiple Sclerosis Patients - Ahmadi, Maryam; Fathi, Farshid; Fouladi, Saloomeh; Alsahebfosul, Fereshteh; Manian, Mostafa; Eskandari, Nahid (Current Molecular Medicine, 2019)
Background: Asthma is a chronic and complex inflammatory disease of the respiratory tract. Also, multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system. Against this background, IL-33 and IL1RL1 play a critical role in autoimmune and inflammatory disorders. Here, we explored the IL-33 serum level and two potential genetic variants in the IL33 gene and its receptor in Iranian asthma and MS patients. Methods: This study consisted of asthma (n=140) and MS patients (n=140), and healthy subjects (n=72). Genotyping was carried out in two genetic polymorphisms, rs1342326 variant of IL-33 and rs10204137SNP variant of IL-33 receptor genes, using High- Resolution Melt Real- Time PCR based method. The level of serum IL-33 was also measured using enzyme-linked immunosorbent assay method. Results: The level of IL33 was significantly higher in asthma and MS patients compared to the control group (P< 0.001- P<0.001).The frequency distribution of the genotype in rs1342326 variant of IL-33 gene in patients with asthma, MS and healthy subjects was not significantly different (P>0.05). The frequency distribution of the genotype in rs10204137 variant of IL-33 gene in MS patients and healthy subjects was significantly different (p = 0.013). Conclusion: Our findings demonstrated that asthma and MS patients had a higher level of IL-33, and IL-33 receptor genetic polymorphism was associated with MS. Further studies in a larger multicenter setting are needed to explore the value of this marker as a risk stratification biomarker.
Keywords: IL-33 serum level